Professional development needs of English teachers in Myanmar university - Kyaw Sein (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
A small-scale survey was conducted in Myanmar to investigate the professional development needs of EFL teachers. The study was to shed light on the current situation and the challenges related to English language education. The participants of the study were asked to select three professional development needs that interested them from a list of ten need areas. Some qualitative data is used to supplement and interpret the results of this study. The results show that the teachers need to take part of the responsibility for their professional development. According to them, ongoing professional development is essential in today’s world. Teachers’ belief in themselves and in what they are doing make them confident. According to the interview data, Myanmar teachers’ preferred PD areas are teaching skills and methods, understanding students, and attending conferences, seminars and workshops.